Special considerations for pediatric vitreoretinal surgery - Nicola Y Gan; Wai-Ching Lam (Taiwan Journal of Ophthalmology, 2018)
In this review, the authors present special considerations a vitreoretinal surgeon should take into account before embarking on surgery in a pediatric eye. First, the anatomy of a pediatric eye is different from an adult and changes as the child grows. This is important especially in relation to the placement of transconjunctival ports. The structural characteristics of the sclera are also different, with lower scleral rigidity found in pediatric eyes. When considering vitrectomy, a posterior pars plicata lens-sparing technique should be considered. However, this may not be possible in complicated total detachments where anterior translimbal vitrectomy may be the method of choice. Scleral buckles are preferred for certain cases, and division of the encirclage is advocated in children below the age of 2 years, once the retina has stabilized. Enzymatic vitreolysis has been described as a preoperative adjunct to enhance complete detachment of the posterior hyaloid and reduce iatrogenic retinal breaks. However, its use in pediatric eyes has been limited, and larger studies are warranted. Finally, postoperative visual rehabilitation and treatment of amblyopia are key to maximizing functional outcomes in the pediatric patient. Co-management with a pediatric ophthalmologist and enlisting the co-operation of the parents are essential.